Actual Frailty Conditions and Lifestyle Changes in Community-Dwelling Older Adults Affected by Coronavirus Disease 2019 Countermeasures in Japan: A Cross-Sectional Study - Tomoyuki Shinohara PhD; Kosuke Saida MS; Shigeya Tanaka PhD; Akihiko Murayama PhD (SAGE Publishing, 2021)
Introduction Because of the countermeasures to prevent the spread of coronavirus disease 2019 (COVID-19) in Japan, it is easy to predict that the suspension of local activities and changes in lifestyle that lead to decreased activity will result in increased frailty and prefrailty rates in older adults. Objective To clarify the actual frailty conditions and lifestyle changes among community-dwelling older adults affected by COVID-19 countermeasures in Japan. Methods This cross-sectional study was conducted between May 8 and June 12, 2020. Self-reported questionnaires were distributed to 1,078 older adults aged ≥65 years. We used the frailty screening index to assess frailty status and developed the Questionnaire for Change of Life (QCL) to assess lifestyle changes, the amount of daily movement, leg muscle strength, meal size, worry or anxiety, and opportunities to talk to people. The differences in prevalence rates of frailty, prefrailty, and robustness between this study and the reference based on the Japanese meta-analysis were verified using the chi-square goodness of fit test. We compared each of the QCL results among the frailty, prefrailty, and robust groups using Fisher's exact test. Results Of 680 older adults (63.1%) analyzed, 60 (8.8%) had frailty and 354 (52.1%) had prefrailty. There was a significant difference between the observed and expected prevalence based on the reference (p = 0.018). The frailty status was significantly associated with lifestyle changes. In participants with frailty, the amount of daily movement, leg muscle strength, and meal size significantly decreased (p < 0.001), whereas worry or anxiety significantly increased (p = 0.040). In contrast, regardless of the frailty status, opportunities to talk to people decreased. Conclusion The prevalence of frailty and prefrailty might have increased due to the effects of COVID-19 countermeasures. Moreover, the lifestyle of community-dwelling older adults affected by COVID-19 countermeasures has changed. Lifestyle changes were more pronounced among older adults with frailty.